Edukasi Siswa-Siswi SDI PAKU Tentang Pola Hidup Sehat - Nur Qadri Rasyid; Tuty Widyanti; Dewi Arisanti (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2020)
Abstract Children are a future asset that must be considered. At school, children cannot control their behavior. They eat and play without supervision so they are very susceptible to their health problems such as diarrhea. The method of implementing community service consists of two stages, namely: 1) the preparation stage including health counseling with the lecture method for SDI Paku students 2) the implementation stages of the program in the form of how to properly process hands and dispose of garbage in its place. The results showed that with the education carried out through counseling about healthy living patterns, SDI Paku students began to apply the habit of washing hands properly and the habit of disposing of garbage in its place.